Gender dan Tingkat kepedulian Masyarakat terhadap Sampah - Susilowati, Tuti; Ashar, Hadi; Kusrini, Ina; Wahyuningsih, Siti; Maretta, Hermasani Tya; Setyaji, Teguh; Purwanti, Purwanti; Ernawati, Dhanik; Widyaningrum, Maria Prasasti Ragil Putri; Sukamsi, Sukamsi; Peluw, Zulfikar (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
Indonesia is the second largest producer of plastic waste in the world after China, one source of waste is from the tourism sector such as in the Borobudur Temple Area, Central Java. The problem of low awareness and gender norms that are still closely embedded in Indonesian society are inhibiting factors in modern approaches to waste management, thereby impacting the burden on local governments in waste management. The aim of this study was to determine the effect of gender on concern for waste. Methods: Cross-sectional deskriptif survey study in the Borobudur sub-district area of 374 respondents representing the X generation or millennial generation and Z generation. This study shows that the difference in the average value (mean) of the variabels of knowledge, concern, perception, millennial PKK actions, and external faktors regarding institutions is slightly higher in the female group, namely 0.5005, 0.2207, 0.1452, 0 .8338, and 0.1046. But, individual perceptions of concern for community groups are slightly higher in the male group, namely 0.0659. This study shows that concern for waste, the female group's average value of each variable is slightly higher than the male group, and only one variable, namely external factors, individual perceptions of concern for community groups is slightly lower.